# f(x)= ((x^3)+(3x^2)+(3x)+1)/((x^2)+(2x)+0) is defined on the interval [-16,17]A. The function f(x) has vertical asympototes at ? B. f(x) is concave down on the region

*print*Print*list*Cite

### 2 Answers

You need to remember that if you need to find the vertical asmptotes to the graph of rational function, you should look for the roots of denominator such that:

`x^2 + 2x = 0`

You need to factor out x such that:

`x(x+2) = 0`

`x = 0 or x + 2 = 0 =gt x = -2`

**Hence, the vertical lines x = 0 and x = -2 are the vertical asymptotes of function.**

b) You need to remember that the graph of function is concave down for f''(x)<0 such that:

`f'(x) = ((x^3+3x^2+3x+1)'*(x^2+2x) - (x^3+3x^2+3x+1)*(x^2+2x)')/((x^2+2x)^2)`

`f'(x) = ((3x^2 + 6x + 3)*(x^2+2x) - (x^3+3x^2+3x+1)*(2x+2))/((x^2+2x)^2)`

`f'(x) = (3x^4 + 6x^3 + 6x^3 + 12x^2 + 3x^2 + 6x - 2x^4 - 2x^3 - 6x^3 - 6x^2 - 6x^2 - 6x - 2x - 2)/((x^2+2x)^2)`

`f'(x) = (x^4 + 4x^3 + 3x^2 - 2x - 2)/((x^2+2x)^2)`

You need to evaluate the second derivative such that:

`f''(x) = ((4x^3 + 12x^2 + 6x - 2)(x^2+2x)^2 - 4(x^2+2x)(x^4 + 4x^3 + 3x^2 - 2x - 2)(x+1))/((x^2+2x)^4)`

`f''(x) = ((4x^3 + 12x^2 + 6x - 2)(x^2+2x) - 4(x^4 + 4x^3 + 3x^2 - 2x - 2)(x+1))/((x^2+2x)^3)`

`4x^5 + 8x^4 + 12x^4 + 24x^3 + 6x^3 + 12x^2 - 2x^2 - 4x - 4x^5 - 4x^4 - 16x^4 - 16x^3 -12x^3 - 12x^2 + 8x^2 + 8x + 8x + 8 = 0`

`24x^3 + 6x^3 + 12x^2 - 2x^2 - 4x - 16x^3 -12x^3 - 12x^2 + 8x^2 + 8x + 8x + 8 = 0`

`-4x^3 + 6x^2 + 12x + 8 = 0`

`2x^3 - 3x^2 - 6x - 4 = 0`

**If `x in [-16,17] =gt f''(x)lt0` , hence the graph of the function is concave down.**

### User Comments

- For function to have a vertical asymptote, it needs to diverge into either when x approaches certain value. And for the function in fractional form, this can be reached by making the denominator 0 while keeping numerator with some value other than 0.

Therefore, x^2+2x=x(x+2)=0

=> x=0 or -2

With each value, numerator doesn't become 0.

Therefore, f(x) has its vertical asymptote at x=0 and x=-2

lim(x->0)f(x) = diverge in positive way,

lim(x->-2)f(x)=diverge in negative way. - f(x) is concave down when f''(x), the second derivative of f(x), has negative value.

f'(x)=(x^4+4x^3+3x^2-2x-20/(x^2(x+2)^2)

f''(x)=(2(x^3+3x^2+6x+4))/(x^3(x+2)^3)<0

Therefore, f(x) is concave down at -1<x<0 or -16<x<-2.

Hope you do great on your work:)